2011
DOI: 10.1038/nn.2900
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal activity modifies the DNA methylation landscape in the adult brain

Abstract: DNA methylation has been traditionally viewed as a highly stable epigenetic mark in post-mitotic cells, however, postnatal brains appear to exhibit stimulus-induced methylation changes, at least in a few identified CpG dinucleotides. How extensively the neuronal DNA methylome is regulated by neuronal activity is unknown. Using a next-generation sequencing-based method for genome-wide analysis at a single-nucleotide resolution, we quantitatively compared the CpG methylation landscape of adult mouse dentate gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
548
2
5

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 611 publications
(584 citation statements)
references
References 51 publications
29
548
2
5
Order By: Relevance
“…22 An increasing number of reports have further proposed that the methylome-transcriptome relationship cannot be represented by a simple model when considering large, high quality datasets. 10,21,23,36,37 In these studies, positive and negative correlations between methylation alterations and transcriptome changes were found only for a minority of CpGs. It was also suggested that the relationship depends on the CpG-content of the promoter region.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…22 An increasing number of reports have further proposed that the methylome-transcriptome relationship cannot be represented by a simple model when considering large, high quality datasets. 10,21,23,36,37 In these studies, positive and negative correlations between methylation alterations and transcriptome changes were found only for a minority of CpGs. It was also suggested that the relationship depends on the CpG-content of the promoter region.…”
Section: Discussionmentioning
confidence: 88%
“…To date, the only previous publication reporting genome-wide dynamic methylome alterations in the field of neurobiology is, to the best of our knowledge, the report by Guo et al 10 Guo et al studied CpGs in genic regions using mixed tissue from the mouse hippocampus after electrostimulation. Our study found, similarly to the observation by Guo et al, that methylome alteration in the adult nervous system can occur rapidly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuronal activation in mouse dentate granule neurons induces dynamic remodeling of genomic DNA methylation profiles, with methylation changes occurring largely outside of CpG islands in association with brain specific genes (27). Although the effect of these methylation changes on gene expression is not known, this work shows that DNA methylation is plastically regulated in response to neuronal activity.…”
Section: Dna Methylation and The Formation Of Long Term And Distant Mmentioning
confidence: 76%
“…DNA methylation has traditionally been viewed as a stable epigenetic mark, however, many recent studies have shown that DNA methylation is plastically regulated, especially in neurons (25)(26)(27). Neuronal activation in mouse dentate granule neurons induces dynamic remodeling of genomic DNA methylation profiles, with methylation changes occurring largely outside of CpG islands in association with brain specific genes (27).…”
Section: Dna Methylation and The Formation Of Long Term And Distant Mmentioning
confidence: 99%